CRESCIMENTO E DESENVOLVIMENTO DO BAMBU TAQUARA IRRIGADO E ADUBADO COM POTÁSSIO E ZINCO - Cunha, Fernando Nobre; Teixeira, Marconi Batista; Cabral Filho, Fernando Rodrigues; Santos, Claudio Carvalho dos; Alves, Daniely Karen Matias; Cunha, Gabriela Nobre (IRRIGA, 2022)
GROWTH AND DEVELOPMENT OF ‘TAQUARA’ BAMBOO IRRIGATED AND FERTILIZED WITH POTASSIUM AND ZINC FERNANDO NOBRE CUNHA1; MARCONI BATISTA TEIXEIRA1; FERNANDO RODRIGUES CABRAL FILHO1; CLAUDIO CARVALHO DOS SANTOS1; DANIELY KAREN MATIAS ALVES1; GABRIELA NOBRE CUNHA2 1Departamento de Hidráulica e Irrigação, Instituto Federal Goiano – Campus Rio Verde, Rodovia Sul Goiana, Km 01, CEP: 75.901-170, Rio Verde – GO, fernandonobrecunha@hotmail.com, marconi.teixeira@ifgoiano.edu.br, fernandorcfilho@hotmail.com, santos.claudiocarvalho@gmail.com, daniely_karen@hotmail.com. 2Gerente de Negócios – Irrigação, Av. Amazonas, n° 1500, Rua 8 - Centro -CEP 77.403-030, Gurupi – TO, gabriela-nc@hotmail.com. 1 ABSTRACT The Americas detain 30% of the total bamboo species, and Brazil is the country holding the greatest diversity. However, characterization and evaluation studies of bamboo species fertilized with potassium and zinc are scarce. The goals of this work were to evaluate growth and development of ‘Taquara’ bamboo plants (Bambusa tuldoides) irrigated and fertilized with potassium and zinc. The experimental design was randomized block, in a split-split-plot arrangement (2 × 2 × 4) with three replications, with two potassium rates in the plots (0 and 80 kg ha-1), two zinc rates in the subplots (0 and 5 kg ha-1), and four evaluation times in the sub-subplots (60, 90, 120, and 150 days after sprouting). Morphological characteristics: plant height, stem diameter, internal stem diameter, stem circumference area, number of internodes, and internode length-were evaluated monthly. Plant height and internode length were measured using a measuring tape; and stem diameter was measured in the middle third of the plant using a caliper ruler. The fertilization with potassium and zinc rates influences the growth and development of ‘Taquara’ bamboo plants (B. tuldoides), promoting increases in most of the analyzed variables. Keywords: Bambusa tuldoides; potassium chloride; zinc sulphate. CUNHA, F. N.; TEIXEIRA, M. B.; CABRAL FILHO, F. R.; SANTOS, C. C.; ALVES, D. K. M.; CUNHA, G. N. CRESCIMENTO E DESENVOLVIMENTO DO BAMBU TAQUARA IRRIGADO E ADUBADO COM POTÁSSIO E ZINCO 2 RESUMO As Américas detêm 30% do total de espécies de bambu e o Brasil é o país que detém a maior diversidade. Entretanto, estudos sobre a caracterização e avaliação de espécies de bambu adubadas com potássio e zinco são escassos. Objetivou-se, no presente trabalho, avaliar o crescimento e desenvolvimento do bambu Taquara (Bambusa tuldoides) irrigado e adubado com potássio e zinco. O delineamento experimental utilizado foi em blocos ao acaso, analisado em esquema de parcelas sub-subdividas 2 × 2 × 4, com três repetições, as parcelas foram compostas por duas doses de potássio (0 e 80 kg ha-1), as subparcelas por duas doses zinco (0 e 5 kg ha-1) e as sub-subparcelas por quatro épocas de avaliações (60, 90, 120 e 150 dias após a brotação). As características morfológicas foram avaliadas mensalmente, quantificando-se: altura de planta (AP); diâmetro de colmo (DC); diâmetro interno do colmo (DI); área da circunferência do colmo (AC); número de entrenós (NE) e comprimento de entrenós (CE). A altura da planta e o comprimento de entrenós foram mensurados com auxílio de uma fita métrica; o diâmetro de colmos foi determinado pelo auxílio de um paquímetro no terço médio da planta. A adubação com doses de potássio e zinco influencia o crescimento e desenvolvimento do bambu Taquara (Bambusa tuldoides), promovendo incrementos na maioria das variáveis analisadas. Palavras-chave: Bambusa tuldoides; cloreto de potássio; sulfato de zinco.